Atmospheric dynamics on tidally locked Earth-like planets in the habitable zone of an M dwarf star. Issue Volume 8:Issue S299(2013) (6th January 2014) - Carone, Ludmila; Keppens, Rony; Decin, Leen
Abstract: We investigated the large scale atmospheric circulation of Gl581g, a potentially habitable planet around an M dwarf star, using an idealized dry global circulation model (GCM) with simplified thermal forcing as a first step towards a systematic extended parameter study. The results are compared with the work of Joshi et al . (1997) who investigated a tidally-locked habitable Earth analogue with less than half the rotation period of Gl581g. The extent, form and strength of the atmospheric circulation in each model generally agree with each other, even though the models differ in key parameters such as planetary radius, surface gravity, forcing scheme and rotation period. The substellar point is associated with an uprising direct circulation-branch of a Hadley-like cell with return flow over the poles. It is compelling to assume that the substellar point of a tidally locked terrestrial exoplanet behaves dynamically like the Earth's tropic associated with clouds and precipitation, making it an ideal target for habitability.